Comparison of The Level of Satisfaction With The Use of Analgesics Ketorolac 30 Mg and Paracetamol 1000 Mg in Moderate Post-Operative Patients - Yosi Budi Setyawan; Meli Rosita (Universitas Islam Negeri Sumatera Utara, Medan, 2024)
Pain is an uncomfortable feeling that can be an emotional experience and has the potential to cause real tissue damage. Post-operative events can cause patients to feel pain in certain parts of the body. In post-operative care to reduce pain, patients are given NSAID (Non-Steroid Anti-Inflammatory Drugs) analgesic drugs, and the drugs commonly used are Ketorolac 30mg and Paracetamol 1000mg. The use of analgesics is said to be effective if the patient's perception shows satisfaction after using the analgesic. The research was conducted to see the level of patient satisfaction in using the analgesic intravenous injection of ketorolac 30mg and intravenous infusion of paracetamol 1000mg. This research used a Randomized Controlled Trial (RCT) design with double blinds. Data collection was carried out in April-July 2021 at PKU Muhammadiyah Gamping Hospital. Then the data obtained was analyzed using the Chi-Square test. There were 40 respondents who met the inclusion and exclusion criteria. The analysis results show a significance value of 0.006<0.05. Thus it can be concluded that there is a difference in satisfaction with the use of analgesics. The research showed that the level of satisfaction with the use of the analgesic intravenous injection Ketorolac 30mg in mild to moderate post-operative patients at PKU Muhammadiyah Gamping Hospital was higher than the use of intravenous infusion Paracetamol 1000mg. We suggest conducting additional research with a larger and more diverse sample to yield results applicable to a broader population. We also recommend the routine use of 30mg ketorolac injection.Keywords : Anti-pain, postperative, satisfaction level